Efficacy and safety of immune checkpoint inhibitors with or without radiotherapy in metastatic non-small cell lung cancer: A systematic review and meta-analysis - Zijing Liu; Zijing Liu; Zijing Liu; Tiankai Xu; Tiankai Xu; Tiankai Xu; Pengyu Chang; Pengyu Chang; Pengyu Chang; Weijia Fu; Weijia Fu; Weijia Fu; et al. (Frontiers Media S.A., 2023)
Background and purpose: Although immune checkpoint inhibitors (ICIs) have become the first-line treatment for metastatic non-small cell lung cancer (mNSCLC), their efficacy is limited. Meanwhile, recent reports suggest that radiotherapy (RT) can activate the systemic antitumor immune response by increasing the release of antigens from tumor tissues. Therefore, in patients with mNSCLC treated with ICIs, investigations were performed to determine whether the addition of RT improved the outcomes. Furthermore, the adverse events rate was evaluated.Methods and materials: Pubmed, Embase, and Cochrane Library were searched using the keywords "radiotherapy," "immune checkpoint inhibitors," and "non-small cell lung cancer" from the date of inception to 2 May 2022. Randomized controlled trials (RCTs) and nonRCTs (NRCTs) comparing the efficacy and safety of RT combined with ICIs versus ICIs alone in metastatic NSCLC were assessed. The primary outcomes were progression-free survival (PFS) and overall survival (OS), and the secondary outcomes were abscopal response rate (ARR), abscopal control rate (ACR), adverse events rate, and pneumonia rate. The analyses were conducted using the Mantel-Haenszel fixed-effects or random-effects model. The I2 statistic was used to determine heterogeneity, whereas funnel plots and Egger's test were used to assess publication bias.Results: In 15 clinical studies, 713 patients received RT combined with ICIs and 1,275 patients received only ICIs. With regard to PFS and OS, the hazard ratios of RT combined with ICIs were 0.79 (0.70, 0.89) and 0.72 (0.63, 0.82), respectively. In terms of ARR and ACR, the odds ratios (ORs) of RT combined with ICIs were 1.94 (1.19, 3.17) and 1.79 (1.08, 2.97), respectively. Subgroup analyses based on study type (RCT/NRCT), RT target (intracranial/extracranial), number of RT sites (single site), previous ICI resistance (yes/no), and sequencing of RT and ICIs (concurrent/post-RT ICIs) revealed that the addition of RT significantly prolonged PFS and OS. However, subgroup analyses based on radiation dose/fractionation indicated that the addition of hypofractionated RT significantly prolonged OS but not PFS. When grouped according to the level of PD-L1 expression, the addition of RT prolonged PFS only in patients who were PD-L1-negative. Furthermore, subgroup analyses of ARR and ACR signified that the combination therapy resulted in better local control of lesions outside the irradiation field in the hypofractionated RT, extracranial RT, and ICI-naïve subgroups. In terms of adverse events, the addition of RT did not significantly increase the adverse events rate but was associated with a higher pneumonia rate [OR values were 1.24 (0.92, 1.67) and 1.76 (1.12, 2.77), respectively].Conclusion: Meta-analysis of existing data suggests that the addition of RT can significantly prolong PFS and OS in patients with metastatic NSCLC receiving ICIs. In addition to lesions in the irradiation field, RT can improve the local control rate of lesions outside the irradiation field via immune activation. Combination therapy does not increase the overall risk of adverse reactions, except for pneumonia.